China And The United States In The South-Antarctic Area. Impacts For Chile And Argentina (2010-- 2025) - Manzano-Iturra, K (UNIV ALBERTO HURTADO, 2025)
In the 21st century, a growing competition between China and the United States is becoming increasingly evident across various sectors of South America. One of them, the southern-Antarctic zone -located in the south of the continent and whose definition was proposed last century by General Ram & oacute;n Ca & ntilde;as Montalva (Chile)- reflects this geopolitical competition between two powers that seek rapprochement, cooperation and competition, especially with Chile and Argentina. Using a qualitative discourse and geopolitical analysis, within a defined time frame (2010-2025), this study aims to examine the impact of China and the United States on this region, which has enormous natural resources, strategic maritime passages, and serves as the gateway to Antarctica.